The Impact of Green Human Resources Management on Employee Productivity at PAM Tirta Mangkaluku in Palopo City - Qhesya Septian; Saharuddin; Rifqa Ayu Dasila (LPPM STMIK Mardira Indonesia, 2026)
The Green Human Resources Management (GHRM) theory in the public sector, which has received limited scholarly attention, effectively supports PAM Tirta Mangkaluku in developing HR policies that enhance productivity and environmental sustainability while promoting a socially responsible workplace culture in line with the Sustainable Development Goals (SDGs). This study aims to examine the impact of Green Human Resources Management on staff productivity at PAM Tirta Mangkaluku in Palopo City. This research utilizes a quantitative methodology through the causal-associative technique. The study population comprises 134 individuals, with sampling conducted using the Slovin formula. The employed data analysis approaches include instrument validation, classical assumption testing, simple linear regression, and hypothesis testing. The findings demonstrate that Green Human Resources Management positively influences employee productivity, albeit to a limited extent. This study shows that Green Human Resources Management enhances employee productivity through green training; however, its effect is somewhat constrained and requires integration with additional human resources management strategies.